Nonlinear dynamic finite element analysis of thick transversely flexible sandwich panel on elastic foundation with account of damage progression in time. Part 2. 3D analysis and time integration - Perel, V.Y. (Проблемы прочности, 2005)
A plate theory for a thick transversely compressible sandwich plate with composite laminated face sheets is constructed using the simplified assumptions earlier described in Part 1. An algorithm, which takes account of damage progression in dynamic problems, is incorporated into the computational scheme based on the geometrically nonlinear formulation and applied to failure analysis o f a sandwich plate under ground impact.